A framework to implement Occupational health and safety innovation - Alfredo Soeiro (2021)
Background and objectives: Being able to compete in the market needs sustainable development. Occupational safety and health Innovation process is one of the most important procedures helping companies to achieve their goal and to win the competition as radical change in the workers' environment, enhancing the profitability of companies. However, most research and discussion of innovations are focused on product development and/or process improvement, disregarding workplace and service innovation. This study will outline the general terms related to safety innovation and how the process can get managed using some techniques to implement a framework in a company. In this case, the objectives of the study are to introduce the innovation in OHS and to introduce a model including some techniques for industries to apply innovation in occupational safety and health. Methodology: To apply Innovation in occupational safety and health, the first step is to indicate the importance of innovation. To do so, a major review of studies focusing on occupational safety and health and innovation were required. The second step in this part is to define a frame work for innovation in safety and health, by reviewing those introduced frameworks in both innovation and health and safety researches. Results and conclusions: As a result, the importance of innovation has been searched and emphasized. On the other hand, a 6 step framework has been introduced and the details of applying the framework has been expanded. The frame work employs 6 continues steps starting by TIPS technique which is followed by JTBD. Based on the result, the framework can be applied. The introduced steps are as follow: Identifying Innovation Projects, Scoping and Focusing Innovation Projects, Leveraging Brainpower and Turbo-Charging Creativity, Selecting the Best Ideas for Further Development and Design, Evaluating How New Products/Services Perform Prior to Their Release, Problem Diagnosis and Improvement Prior to Commercialization. Following these steps as a framework may increase the efficiency of the company however, there is a huge need of several case studies in long term to assess the result and to compare the efficiency of the introduced framework.